2013
DOI: 10.1016/j.bmcl.2013.08.103
|View full text |Cite
|
Sign up to set email alerts
|

Lead optimization of an acylhydrazone scaffold possessing antiviral activity against Lassa virus

Abstract: Previously we reported the optimization of antiviral scaffolds containing benzimidazole and related heterocycles possessing activity against a variety of arenaviruses. These series of compounds were discovered through an HTS campaign of a 400,000 small molecule library using lentivirus-based pseudotypes incorporated with the Lassa virus envelope glycoprotein (LASV GP). This screening also uncovered an alternate series of very potent arenavirus inhibitors based upon an acylhydrazone scaffold. Subsequent SAR ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…We demonstrated that phenothrin has activity against MOPV, GTOV, and CHPV, with IC 50 values lower than 10 μM. The structure of phenothrin is similar to that of the LASV specific entry inhibitor ST-161, which uses a cyclopropyl N -acylhydrazone as a scaffold (26,44). In our study, resistant viruses for LASV or GTOV were not successfully generated in the presence of phenothrin, suggesting this drug is less prone to induce adaptive mutations in the glycoprotein.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…We demonstrated that phenothrin has activity against MOPV, GTOV, and CHPV, with IC 50 values lower than 10 μM. The structure of phenothrin is similar to that of the LASV specific entry inhibitor ST-161, which uses a cyclopropyl N -acylhydrazone as a scaffold (26,44). In our study, resistant viruses for LASV or GTOV were not successfully generated in the presence of phenothrin, suggesting this drug is less prone to induce adaptive mutations in the glycoprotein.…”
Section: Discussionmentioning
confidence: 81%
“…Lacidipine is a lipophilic dihydropyridine calcium antagonist. Since calcium channels proved to be a therapeutic target for other enveloped viruses and calcium inhibitors showed promising effects on the entry of the closely-related JUNV and EBOV (22,42-44), we investigated whether lacidipine inhibits LASV entry by acting as a calcium inhibitor. To address this, we first reviewed all 22 calcium inhibitors included in the current FDA drug library; results showed that in addition to lacidipine, only two calcium inhibitors moderately inhibited LASV entry, including diltiazem and cilnidipine.…”
Section: Discussionmentioning
confidence: 99%
“…The advent of arenavirus reverse genetics and recombinant pseudotype platforms allowed successful screening of small molecule libraries for entry inhibitors. These screens identified a panel of potent direct antiviral agents that target predominantly viral entry and show distinct specificities among arenaviruses (71,(75)(76)(77)(78)(79)(80)(81). A complementary approach involves the identification of cellular factors required for productive viral entry and their evaluation as antiviral drug targets.…”
Section: Discussionmentioning
confidence: 99%
“…4). Furthermore, photoaddition was also blocked by the addition of excess ST-161 and ST-193, two independently identified SIGA fusion inhibitors that are respectively selective for LASV (33) or broadly active against NW and OW arenaviruses (32) (Fig. 6A).…”
Section: Figmentioning
confidence: 99%
“…High-throughput screening campaigns at SIGA Technologies (31)(32)(33)(34) and the Scripps Research Institute (35,36) have recently identified six chemically distinct classes of small-molecule compounds that specifically antagonize pH-induced activation of GPC membrane fusion to prevent arenavirus entry into its host cell (37,38). Several of these inhibitors have been shown to protect against lethal arenavirus infection in small-animal models (31,39).…”
mentioning
confidence: 99%